Uniqueness of solutions of the Cauchy problems for first order partial differential-functional equations - Danuta Jaruszewska-Walczak (Le Matematiche, 1994)
We formulate a criterion of uniqueness of solutions of a Cauchy problem using the comparison function of the Kamke type. This will be a generalization of classical results concerning first order equations with partial derivatives. We prove that the uniqueness criteria of Perron and Kamke type for differential-function problems are equivalent if given functions are continuous.